2015
DOI: 10.1371/journal.pone.0140782
|View full text |Cite
|
Sign up to set email alerts
|

Elisidepsin Interacts Directly with Glycosylceramides in the Plasma Membrane of Tumor Cells to Induce Necrotic Cell Death

Abstract: Plasma membrane integrity is essential for cell life. Any major break on it immediately induces the death of the affected cell. Different molecules were described as disrupting this cell structure and thus showing antitumor activity. We have previously defined that elisidepsin (Irvalec®, PM02734) inserts and self-organizes in the plasma membrane of tumor cells, inducing a rapid loss of membrane integrity, cell permeabilization and necrotic death. Here we show that, in sensitive HCT-116 colorectal cells, all th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…Elisidepsin ( 357 ) also underwent clinical development after showing IC 50 values between 0.4 and ~9 μM in a 23 cancer cell lines, including breast, colon, head and neck, lung, ovary, pancreas, prostate, and melanoma types [ 810 , 811 , 812 ]. Elisidepsin ( 357 ) acts at the cell membrane level, interacting directly with glycosylceramides in the membrane of cancer cells, while inducing necrosis-like cell death in the yeast Saccharomyces cerevisiae [ 813 , 814 , 815 ]. Elisidepsin ( 357 ) is active in vivo against human melanoma, liver, pancreas, breast, and prostate cancer xenografts [ 816 ].…”
Section: Pharmacological Activitymentioning
confidence: 99%
“…Elisidepsin ( 357 ) also underwent clinical development after showing IC 50 values between 0.4 and ~9 μM in a 23 cancer cell lines, including breast, colon, head and neck, lung, ovary, pancreas, prostate, and melanoma types [ 810 , 811 , 812 ]. Elisidepsin ( 357 ) acts at the cell membrane level, interacting directly with glycosylceramides in the membrane of cancer cells, while inducing necrosis-like cell death in the yeast Saccharomyces cerevisiae [ 813 , 814 , 815 ]. Elisidepsin ( 357 ) is active in vivo against human melanoma, liver, pancreas, breast, and prostate cancer xenografts [ 816 ].…”
Section: Pharmacological Activitymentioning
confidence: 99%
“…The anticancer compound elisidepsin is an analogue of kahalalide F, which exhibited in vitro activity against several tumor cell lines such as breast, colon, pancreas, prostate, and lung [ 54 , 55 , 56 ]. It showed promising results for further clinical studies of cancer therapy.…”
Section: Natural Cyclic Peptides and Analogues In Clinical Trialsmentioning
confidence: 99%
“…Elisidepsin was shown to insert into the plasma membrane of cancer cells and reorganize itself in the membrane; this caused the disruption of the plasma membrane and resulted in a loss of integrity of the membrane, causing necrotic death of cells [ 192 , 205 ]. Molina-Guijarro et al [ 206 ] elucidated the detailed mechanism of loss of membrane integrity by elisidepsin and identified that glycosylceramides act as membrane targets of elisidepsin. Glycosylceramides in cells facilitates the insertion of elisidepsin, resulting in membrane destabilization and cell death.…”
Section: Drugs On the Market And In Clinical Trialsmentioning
confidence: 99%